Relationships between general self-efficacy, number of counselling sessions, mandated counselling satisfaction and readiness to change among institutionalised adolescents in Malaysia - Muhammad Shariff Paul, Azzah Sabrina (2015)
Readiness to change is the first step towards a successful behaviour modification in a treatment programme. It is associated with higher self-efficacy and higher satisfaction. Various literatures suggest association between selfefficacy and satisfaction on readiness to change, also the association of number of treatment sessions with positive treatment outcome, but fail to measure the relationship of these three variables together. Furthermore, the popularity of mandated counselling as part of behavioural treatment among institutionalised adolescents in Malaysia strengthens the justification of the current research. Hence, the current research determined to study the relationships between general self-efficacy, number of counselling sessions, mandated counselling satisfaction and readiness to change among institutionalised adolescents in Malaysia. Quantitative correlational research design was used, where a total of 365 institutionalised adolescents were selected from seven rehabilitation institutions across Malaysia using cluster sampling method. A set of self-administered questionnaires were used to collect information related to institutionalised adolescents‟ demographic characteristics information, general self-efficacy measured using General Self-Efficacy Scale (Schwarzer & Jerusalem, 1995), and mandated counselling satisfaction and readiness to change, measured using Mandated Counselling Satisfaction Scale (Mansor, Rumaya & Zainal, 2013) and University of Rhode Island Change Assessment (Prochaska & DiClemente, 1982) respectively. Descriptive analysis revealed that 65.8% institutionalised adolescents were contemplating to change behaviour, 52.9% were in the high general self-efficacy category and 53.4% were experiencing high level of mandated counselling satisfaction. Bivariate analysis displayed significant strong relationships between general self-efficacy, number of counselling sessions, mandated counselling satisfaction, and readiness to change. Furthermore, multiple regression analysis showed that 64% of variation in readiness to change was explained by the predictors, where mandated counselling satisfaction variable was the most significant predictor in determining readiness to change. Finally, mediation analysis for general selfefficacy and number of counselling sessions revealed partial mediation effect, where the relationships between mandated counselling satisfaction and readiness to change were reduced to .04 and .02 when controlling general selfefficacy and number of counselling sessions variable respectively. Sobel Test also confirmed the mediation effect of both variables. In conclusion, general self-efficacy and number of counselling sessions were the key towards facilitating institutionalised adolescents‟ readiness to change. The findings provide significant information on ways to improve institutionalised adolescents‟ behaviour moditication treatment in Malaysia.